The Impact of Information Technology Integration on the Decision-Making Process - Rajaa Nouri Hussein; Ghalia Nassreddine; Joumana Younis (Journal of Techniques)
In the last decade, information technology tools have witnessed enormous development. Nowadays, they are used in all daily human tasks. Organizations and companies have recently started using information technology tools in all sectors. For example, the decision-making process is an essential task in all organizations. By using information technology components, companies can create a decision-making system that produces more accurate results with less time, effort, and cost. In this paper, the authors describe the role of information technology tools in the decision-making process. The impact of using information technology in the decision-making process was studied at a telecommunications company in Iraq. The authors use a descriptive-analytical method to describe this impact. They adopt a questionnaire to collect information and answer it. The analysis of the answers is done using SPSS. The findings indicate a link between using information technology tools and making sound decisions.